2008
DOI: 10.1016/j.apm.2007.09.026
|View full text |Cite
|
Sign up to set email alerts
|

A multi-objective wholesaler–retailers inventory-distribution model with controllable lead-time based on probabilistic fuzzy set and triangular fuzzy number

Abstract: This paper develops a single wholesaler and multi retailers mixture inventory distribution model for a single item involving controllable lead-time with backorder and lost sales. The retailers purchase their items from the wholesaler in lots at some intervals throughout the year to meet the customers' demand. Not to loose the demands, the retailers offer a price discount to the customers on the stock-out items. Here, it is assumed that the lead-time demands of retailers are uncertain in both stochastic and fuz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Since some of the evaluation criteria are subjective and qualitative in nature, it is difficult for decision makers to express the preferences using exact numerical values. In many practical cases, an overall triangular fuzzy numbers (TFNs) are used to effectively aggregate the assessment of the decision makers to each criterion [26][27][28][29]. Moreover, interval-valued triangular fuzzy numbers can provide a more accurate modeling to encounter with the problems and improve emergency response plans for chemical contingency spills [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Since some of the evaluation criteria are subjective and qualitative in nature, it is difficult for decision makers to express the preferences using exact numerical values. In many practical cases, an overall triangular fuzzy numbers (TFNs) are used to effectively aggregate the assessment of the decision makers to each criterion [26][27][28][29]. Moreover, interval-valued triangular fuzzy numbers can provide a more accurate modeling to encounter with the problems and improve emergency response plans for chemical contingency spills [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…For the JRD policy, it is necessary to decrease the total cost while improving the service level. Although there are several papers that studied multiobjective inventory models (Roy and Maiti [ 16 ]; Rong et al [ 17 ]; Islam [ 18 ]; Wee et al [ 19 ]), no study on the multiobjective JRD can be found.…”
Section: Introductionmentioning
confidence: 99%
“…Many linear or nonlinear weighted methods (Rong et al [ 17 ]; Islam [ 18 ]; Wee et al [ 19 ]; Roy and Maiti [ 16 ]) were used to convert the multiobjective to a single one in the existing studies. These methods undoubtedly provide one easy way to deal with the multiobjective JRD model.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Dey and Chakraborty [9] developed a fuzzy random periodic review model with variable lead-time. Rong et al [10] studied a multi-objective inventory model with controllable lead-time and triangular fuzzy numbers. Jauhari et al [11] introduced a fuzzy periodic review model involving stochastic demand.…”
mentioning
confidence: 99%